Conflictos entre Wellington y los gobernadores de Portugal durante la campaña de 1810-1811 contra Masséna - Dores Costa, Fernando (Cuadernos de Historia Moderna, 2011)
This paper is the preliminary result of a re-examination of the conflict between Lord Wellington, supreme commander of the British and Portuguese military forces, and some members of the Portuguese council of governors, in particular the Principal Sousa, brother of the most influential minister of the cabinet of king D. João, resident with his Court in Brazil since 1808. The background of the conflict was the tactical system conceived by Wellington in 1809 in order to resist to any new French offensive -the construction of the famous “lines of Torres Vedras” and therefore to build up a kind of “artificial island” around Lisbon. Sousa opposed the plan and its costs -scorched-earth policy. Wellington blamed Sousa as the main responsible for all the problems he had to face during the campaign of 1810-1811. However, it is hard to believe that the problem was the personality or the political influence of Sousa. The main difficulty was the subordination of the Portuguese administration to the British military goals in the Peninsula.
Keywords: Wellington tactical thought; The “Torres Vedras lines”; Napoleonic imperial system; Portuguese Regency